Electromagnetic Compatibility Design and Optimization Strategies for High-Frequency Ultrasonic Power Supplies - Liang, Zhen (International Journal of Engineering Advances, 2025)
Electromagnetic compatibility (EMC) design of high-frequency ultrasonic power supplies is crucial for ensuring their performance and reliability. This review discusses common EMC design strategies for high-frequency ultrasonic power supplies, including shielding design, grounding and electromagnetic isolation, and layout optimization. Special emphasis is placed on the role of the three-stage EMI filter in reducing electromagnetic interference (EMI) and improving power supply performance. Through a detailed analysis of the filter design, its effectiveness in suppressing low, medium, and high-frequency noise is demonstrated. Additionally, the paper explores the application of novel materials and technologies for EMC optimization and looks ahead to future development trends.